First-principles study on the electronic, mechanical and optical properties for silicon allotropes in hexagonal 2–7 stacking orders. (October 2022) - Wei, Yalan; Li, Jiaxin; Shi, XiZhi; Li, Jin; He, Chaoyu
Abstract: Element silicon can form many allotropes due to its sp 3 -hybridization and its ground state phase in 3C stacking order (Si-I) is the material pioneer of solar cells and the material basis for micro-electronics. In this work, we proposed five new silicon allotropes (5H, 6H-2, 7H-1, 7H-2 and 7H-3) with similar stacking manners to Si-I but in different orders by random sampling strategy combined with group and graph theory (RG 2 ). The calculated total energies of these five new silicon allotropes are just a few meV/atom higher than that of the Si-I and all of them are confirmed to be both dynamically and mechanically stable based on their vibrational and mechanical properties. The crystalline structures and fundamental physical properties discussed in present work are useful for future experiments to explain potential hexagonal silicon allotropes beyond 3C. Graphical Abstract: Image, graphical abstract